Identifying childhood correlates of adult purpose and meaning across 22 countries (Global Flourishing Study) - Eric S. Kim; Matt Bradshaw; R. Noah Padgett; Ying Chen; Koichiro Shiba; James L. Ritchie-Dunham; Brendan W. Case; Byron R. Johnson; Tyler J. VanderWeele (npj Mental Health Research)
Abstract How might we cultivate a life imbued with purpose and meaning? Though common experience indicates purpose and meaning are inherently important, empirical evidence confirms they are also linked to improved health/well-being. However, childhood antecedents of purpose and meaning in adulthood are understudied. We analyzed nationally representative data from 22 countries in the Global Flourishing Study (N = 202,898) and evaluated whether 11 aspects of a child’s upbringing correlate with purpose and meaning in adulthood, and if these associations vary by country. Some childhood factors were associated with increased purpose and meaning, including: good health, good relationship with parents, economic stability, regular religious service attendance, being female, and older birth cohorts. Childhood factors associated with decreased purpose and meaning included: abuse, feeling alienated, poor health, economic hardship, and loss of a parent. These findings may inform the development of programs designed to foster purpose and meaning that are globally adaptable and locally nuanced.